THE EFFECT OF SCHOOL CONNECTEDNESS ON SCHOOL WELL-BEING IN STUDENTS AT MUHAMMADIYAH 7 SURABAYA HIGH SCHOOL - Muflih, Muhammad; Fahmawati, Zaki Nur (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine the effect that school connectedness has on school well-being in Muhammadiyah 7 Surabaya high school students. School connectedness acts as the dependent variable, while school well-being acts as the independent variable. Method: This type of research is quantitative research with a correlational approach. The population in this study were 109 students. The sample in this study involved the entire population determined using saturated sampling technique. The data collection technique used was using a psychological scale measuring instrument consisting of a school well being scale with a reliability value of 0.769 and a school connectedness scale with a reliability value of 0.887. Data analysis in this study used simple regression utilizing the SPSS version 26 computer program. Results: The results of this study showed a positive and significant influence between school connectedness on school well-being at SMA Muhammadiyah 7 Surabaya. Based on anova testing (F test), the score is 75.035 with a significance value of p < 0.001. Novelty: This research is useful for filling the gap of previous research by linking between 2 variables, namely school connectedness and school well being.